Using Coconut Water to Control Addiction - Ahajumobi, N. E.; Oparaocha, E. T.; Chike, E.; Eteike, P. (European Journal of Applied Sciences, 2025)
Introduction: Relapse from nicotine and other addictive substances prevented people from quitting and contributed to mental-health problems, academic decline, and increased risk-taking. Objective: To determine whether coconut juice could help individuals addicted to drugs or alcohol quit successfully. Methods: This experimental study used systematic random sampling to recruit participants and assign them to three groups: a control group (I) and two treatment groups (II and III). Group II received coconut water, and Group III received a nicotine-cessation vape; all three groups served as comparison groups. Participants used journals to record treatments received and amounts of addictive substances consumed. Only individuals willing to quit were included to reduce attrition. Data were analyzed with SPSS. ANOVA assessed within- and between-group differences; Tukey HSD tested significance; and bivariate regression examined relationships and causal direction. Results: With a 5% error margin and 95% CI, p value was set at .05. So, values ≥ .05 H0 to be accepted meaning no relationship, and values ≤ .05 H0 to be rejected. Results showed that p-values were far less than .0001<.05 thus, H ₀ was rejected and H ₐ accepted because there was very strong relationship. Conclusion: Coconut-water treatment showed a very strong statistical and practical significant difference and a meaningful relationship with addiction control.